Economic impact of road transportation infrastructure projects: the case of Egnatia Odos Motorway. Issue 4 (3rd April 2023) - Magoutas, Anastasios; Manolopoulos, Dimitris; Tsoulfas, Giannis T.; Koudeli, Maria
ABSTRACT: Non-cyclical and high-leverage infrastructure projects, such as road transportation networks, have been considered as critical policy instruments to promote growth and social development. Yet, their growth-generating effect on the economic welfare of countries and regions has come under scrutiny in recent years: several studies have nuanced the implicit positive associations between investments in transportation and economic benefits. Building upon a set of traffic flow characteristics as potential correlates to the regional development indicator, this research focuses on the economic impacts of Egnatia Odos Motorway (EOM) on Greece's Northern region. To specify, by employing a large-scale longitudinal dataset which includes over 230 million entry records of various vehicle types along EOM, generated from toll collection systems between 2010 and 2019, we investigate the associations between traffic data and potential variations in regional GDP per capita annual growth rate. Our results suggest positive associations between regional economic development and the EOM operation and, more specifically, with passengers' transportation and inland freight. We conclude that transportation big data provide essential input for the appraisal of a road transport investment project, reveal the status of regional welfare, and may contain valuable information for spatial management and planning.